A Study on q-Starlike Functions Connected with q-Extension of Hyperbolic Secant and Janowski Functions - Pengfei Bai; Adeel Ahmad; Akhter Rasheed; Saqib Hussain; Huo Tang; Saima Noor (Mathematics, 2025)
This study introduces a novel subclass of q-starlike functions that is defined by the application of the q-difference operator and q-analogue of hyperbolic secant function. By making certain variations to the parameter “q”, the geometric interpretation of the domain hyperbolic secant function has also been discussed. The primary objective is to investigate and establish key results on the differential subordination of various orders within this newly defined class. Furthermore, convolution properties are explored and coefficient bounds are derived for these functions. A deeper analysis of these coefficients bounds unveils intriguing geometric insights and significant mathematical problems.